COMMUNITY CULTURAL CHALLENGES IN IMPLEMENTING THE TUBERCULOSIS ERADICATION PROGRAM AT BERINGIN SAKTI COMMUNITY HEALTH CENTER 2023-2024: Tantangan Budaya Masyarakat dalam Implementasi Program Pemberantasan Tuberkulosis di Puskesmas Beringin Sakti 2023-2024 - Rizki Syafril; Yarsi Dafrianita (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
The tuberculosis control program at Beringin Sakti Health Center represents a national public health strategy aimed at reducing the incidence and impact of one of the world’s deadliest infectious diseases. However, the effectiveness of this program is significantly hindered by deep-rooted cultural beliefs in communities such as Nagari Taratak Tinggi, West Sumatra. This qualitative descriptive study explores how cultural values, traditional healing practices, and local authority figures affect the implementation of the program. Using in-depth interviews, observation, and document analysis involving 12 informants—including health workers, TB patients, traditional healers, and community leaders—the study finds that tuberculosis is often perceived as a mystical illness caused by supernatural forces, leading people to seek help from shamans rather than medical professionals.The study employs Grindle’s implementation model to analyze the mismatch between policy content and local context. Top-down approaches, lack of cultural sensitivity, and exclusion of local leaders from the planning process contribute to low public engagement and trust. The findings suggest that TB programs must adopt a participatory, culture-based approach by involving traditional and religious figures, using locally meaningful narratives, and promoting respectful, persuasive health communication to bridge the gap between biomedical interventions and local belief systems.